Cumulative risk and developmental health: an argument for the importance of a family‐wide science. Issue 4 (8th April 2015) - Browne, Dillon T.; Plamondon, Andre; Prime, Heather; Puente‐Duran, Sofia; Wade, Mark
<x xml:space="preserve">Abstract</x> A substantial body of research links social disadvantage and developmental health via a cascade running from poverty, to cumulative psychosocial risk, to disrupted family dynamics, to child biological regulatory systems and neurocognitive processing, and finally to morbidity across the lifespan. Most research in this area employs single‐dyad or between‐family methodology. While informative, there are limitations to this approach. Specifically, it is impossible to determine how risk alters psychosocial environments that are similar for all persons within a household, versus processes that are unique to particular children. This is important in light of literature citing the primacy of child‐specific environments in driving developmental health. Methodologically speaking, there are both benefits and challenges to family‐wide approaches that differentiate between‐ and within‐family environments. This review describes literature linking cumulative risk and developmental health via family process, while articulating the importance of family‐wide approaches. Areas of shortcoming and recommendations for a family‐wide science are provided. WIREs Cogn Sci 2015, 6:397–407. doi: 10.1002/wcs.1349 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have no conflicts of interest to disclose.